Exploring violent cosmologies from a "radical interactionist" approach - Ceretti, Adolfo (Critical criminology, 2022)
This article advances a theoretical perspective on violent crime, using interviews with male prisoners in Italy who had perpetrated violence. By drawing on Athens’ (1992, 1997, 2007, 2017) "radical interactionism," we propose the concept of "violent cosmology" in order to counter linear explanations of cause and effect. In an effort to complement narrative criminologists’ contributions, we seek to recognize and understand the dimensions of meaning that are accessed by social actors when they prepare and carry out a violent act, exploring the psycho-social processes that animate violent social experiences from the perspectives of perpetrators. Specifically, we suggest that a "radical interactionist" approach, in dialogue with narrative criminology, can help (1) illuminate the sources of perpetrators’ narratives; (2) explore the interplay between individuals and social structures; and (3) investigate ambiguities in the narratives of violent actors. Finally, we examine how enhancing the reflexivity of violent actors and recognizing the specificity and integrity of their lives and social experiences is a necessary precondition for understanding violent crime.